Neutralization of oxidized phospholipids attenuates age‐associated bone loss in mice. Issue 8 (19th July 2021) - Palmieri, Michela; Almeida, Maria; Nookaew, Intawat; Gomez‐Acevedo, Horacio; Joseph, Teenamol E.; Que, Xuchu; Tsimikas, Sotirios; Sun, Xiaoli; Manolagas, Stavros C.; Witztum, Joseph L.; Ambrogini, Elena
Abstract: Oxidized phospholipids (OxPLs) are pro‐inflammatory molecules that affect bone remodeling under physiological conditions. Transgenic expression of a single‐chain variable fragment (scFv) of the antigen‐binding domain of E06, an IgM natural antibody that recognizes the phosphocholine (PC) moiety of OxPLs, increases trabecular and cortical bone in adult male and female mice by increasing bone formation. OxPLs increase with age, while natural antibodies decrease. Age‐related bone loss is associated with increased oxidative stress and lipid peroxidation and is characterized by a decline in osteoblast number and bone formation, raising the possibility that increased OxPLs, together with the decline of natural antibodies, contribute to age‐related bone loss. We show here that transgenic expression of E06‐scFv attenuated the age‐associated loss of spinal, femoral, and total bone mineral density in both female and male mice aged up to 22 and 24 months, respectively. E06‐scFv attenuated the age‐associated decline in trabecular bone, but not cortical bone, and this effect was associated with an increase in osteoblasts and a decrease in osteoclasts. Furthermore, RNA‐seq analysis showed that E06‐scFv increased Wnt10b expression in vertebral bone in aged mice, indicating that blocking OxPLs increases Wnt signaling. Unlike age‐related bone loss, E06‐scFv did not attenuate the bone loss caused by estrogen deficiency or unloading in adult mice. These results demonstrate that OxPLs contribute to age‐associated bone loss. Neutralization of OxPLs, therefore, is a promising therapeutic target for senile osteoporosis, as well as atherosclerosis and non‐alcoholic steatohepatitis (NASH), two other conditions shown to be attenuated by E06‐scFv in mice. Abstract : During aging, oxidized phospholipids (OxPL) increase, while IgM natural antibodies, which recognize OxPL, decrease. Transgenic expression of E06‐scFv, an IgM natural antibody fragment that recognizes the phosphocholine (PC) moiety of OxPL, attenuates the age‐related bone loss and increases Wnt10b expression in the bone of aged mice. OxPL contribute to age‐associated bone loss, and neutralization of OxPL is a promising therapeutic target for senile osteoporosis.